2013
DOI: 10.1371/journal.pone.0074526
|View full text |Cite
|
Sign up to set email alerts
|

MR Volumetric Study of Piriform-Cortical Amygdala and Orbitofrontal Cortices: The Aging Effect

Abstract: IntroductionThe piriform cortex and cortical amygdala (PCA) and the orbitofrontal cortex (OFC) are considered olfactory-related brain regions. This study aims to elucidate the normal volumes of PCA and OFC of each age groups (20.0-70.0 year old), and whether the volumes of PCA and OFC decline with increasing age and diminishing olfactory function.MethodsOne hundred and eleven healthy right-handed participants (54 males, 57 females), age 20.0 to 70.0 years were recruited to join this study after excluding all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
5
10
0
Order By: Relevance
“…We know that facial recognition and social motivation processes are altered in people with ASD and have been associated with altered patterns of brain activity [51][52][53]. Interestingly, odor valence has also been linked to neural activity in the orbitofrontal cortex [54][55][56]. That we also observed a relationship between odor identification and valence lends further support to the implication of the orbitofrontal cortex in both social and olfactory symptoms of ASD.…”
Section: Discussionsupporting
confidence: 74%
“…We know that facial recognition and social motivation processes are altered in people with ASD and have been associated with altered patterns of brain activity [51][52][53]. Interestingly, odor valence has also been linked to neural activity in the orbitofrontal cortex [54][55][56]. That we also observed a relationship between odor identification and valence lends further support to the implication of the orbitofrontal cortex in both social and olfactory symptoms of ASD.…”
Section: Discussionsupporting
confidence: 74%
“…In some structural MRI studies, the amygdala shows no significant differences in volume across the adult lifespan, in the context of decline in other structures (Jernigan et al, 2001, Jiang et al, 2014, Li et al, 2014, Shen et al, 2013). A post-mortem study also showed no significant decrease in volume with age (Brabec et al, 2010).…”
Section: The Fate Of Emotion-related Brain Regions and Monoaminergic mentioning
confidence: 97%
“…Human morphometrical studies using magnetic resonance imaging (MRI) have yielded mixed results. One study suggests that among the olfactory-related brain structures, the volume of the piriform cortex and that of the amygdala cortex do not reduce with age, while the volume of the orbitofrontal cortex significantly decreases (Shen et al, 2013 ). Another study examining normal subjects across ages showed that the volume of the OB and tract showed an initial increase up to the 4th decade of life, followed by a decrease with increasing age (Yousem et al, 1998 ).…”
Section: Age-related Changes In the Central Olfactory Pathway And Olfmentioning
confidence: 99%